Methodological issues for the economic evaluation of health interventions: a concise state of the art - Gian Luca Di Tanna; Gianluca Baio (Epidemiology, Biostatistics and Public Health)
This paper presents a preliminary report of the Italian Society of Medical Statistics and Clinical Epidemiology (SISMEC) working group called SiPrEMAS (Evidence Synthesis and Decision Modelling in Health) collating some topics addressed throughout the first two years of collaboration. It contains a rapid overview of the principal methods used for the economic evaluation of health interventions. Special focus is given to the process of assembling and pooling the available evidence, modeling methods, the analysis of uncertainty (structural and on parameters), cost analysis and cost consequences analysis. This paper intends to stimulate the discussion among different professionals involved in the decision making process at national level, trying to (re)bridge the gap between decision makers and researchers.